Ateliê de Teatro Circulando in zinc anniversary (Revista Aspas, 2022)
This paper presents the “Oficina de Teatro Circulando: a theater atelier for youth with mental disorders,” an extension project that takes place at Escola de Teatro, Federal University of the State of Rio de Janeiro. The study focuses on the desires and challenges surrounding the workshop, such as continuity of work during the COVID-19 pandemic, the execution of project events and the initial discussions regarding racial issues within the project. Moreover, this article reaffirms the importance of neurodivergent individuals occupying their rightful spaces, starring in their stories and putting their voices and bodies out into the world.